Preparation method of iron-based nano laccase and application of iron-based nano laccase in removal of organic pollutants

Preparation of iron-based nanolaccase by sol-gel method solves the problem of difficult control of particle uniformity and crystallinity in the prior art, improves catalytic activity and stability, simplifies the process and reduces costs, and achieves more efficient nanomaterial preparation.

CN119215893APending Publication Date: 2024-12-31SUZHOU SAIZHIXIN TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411226568.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing iron-based nanolaccase preparation methods are difficult to control the uniformity and crystallinity of particles, resulting in reduced catalytic activity and stability, and are complex and costly, limiting large-scale production and commercial applications.

Method used

Iron-based nanolaccase was prepared by sol-gel method, and gels with a three-dimensional network structure were formed by hydrolysis and polymerization. Then, Fe3O4-based nanoenzyme was dried and heat-treated to form, and purified by grinding and ultrasonic dispersion, using X-ray diffraction, etc. Characterization is performed by means of optimizing the structure and performance of nanoparticles.

Benefits of technology

The purity and crystallinity of iron-based nanolaccase are improved, the preparation process is simplified, the production cost is reduced, the catalytic performance and production efficiency are improved, and a more economical and environmentally friendly preparation method is realized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215893A_ABST
    Figure CN119215893A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of iron-based nano laccase and application of the iron-based nano laccase in removal of organic pollutants, and relates to the technical field of iron-based nano laccase, and the preparation method comprises the following steps: S1, preparing a precursor solution; s2, carrying out sol-gel conversion; s3, drying and heat treatment; s4, obtaining of nano laccase; and S5, purification and characterization. According to the preparation method of the iron-based nano laccase and the application of the iron-based nano laccase in removing the organic pollutants, the preparation process of the iron-based nano laccase is optimized, the synthesis method of the iron-based nano laccase is improved, the purity and the crystallinity of iron-based nano particles are improved by adopting a sol-gel method, and the iron-based nano laccase is prepared by utilizing advanced nanotechnology and characterization means such as a transmission electron microscope and X-ray diffraction. The structure, the morphology and the surface property of the nano-enzyme are accurately regulated and controlled, so that specific catalytic performance is realized, the whole preparation method is simpler, more economical and more environment-friendly, the production cost is reduced, and the production efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of iron-based nano-laccase, in particular to a preparation method of an iron-based nano-laccase and application thereof in removing organic pollutants. Background Art

[0002] Iron-based nanolaccase is not a natural laccase in the traditional sense, but an iron-based nanomaterial synthesized using nanotechnology to simulate the function of laccase (a copper-containing polyphenol oxidase). Iron-based nanomaterials have received extensive attention in the study of enzyme mimics due to their good catalytic activity, low cost and stability. As one of these materials, iron-based nanolaccase aims to achieve redox catalytic ability similar to laccase through nanoscale design and optimization.

[0003] For example, the patent document with publication number CN116099572A discloses a method for preparing an iron-based nanozyme. The invention proposes an iron-based nanozyme that can catalyze a luminescent system represented by luminol to produce a luminescent signal; the nanozyme has strong catalytic activity, good stability, strong environmental tolerance and low cost, and can replace natural enzymes to catalyze the luminescence of the luminol system; the nanozyme and the luminol system are combined to construct a chemiluminescent sensor to achieve highly sensitive detection of multiple targets.

[0004] However, the existing iron-based nano-laccase preparation process similar to the above application still has the following shortcomings:

[0005] However, the existing preparation methods of iron-based nanolaccases are difficult to fully control the uniformity and crystallinity of the particles during the synthesis process, so that iron-based nanoparticles (such as Fe 3 O 4 The purity and crystallinity of NPs are reduced, thus affecting the catalytic activity and stability of the prepared iron-based nanolaccase. Secondly, the existing preparation methods of iron-based nanolaccases usually involve complex chemical synthesis processes and high costs, which limits their feasibility in large-scale production and commercial applications. At present, there is still a lack of simpler, more economical and environmentally friendly preparation methods.

[0006] Therefore, there is an urgent need to improve this shortcoming. The present invention studies and improves the existing technology and its shortcomings, and provides a preparation method of an iron-based nano-laccase and its application in removing organic pollutants. Summary of the invention

[0007] The purpose of the present invention is to provide a preparation method of an iron-based nano-laccase and its application in removing organic pollutants, so as to solve the problems raised in the above background technology.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] In a first aspect, a method for preparing an iron-based nano-laccase comprises the following steps:

[0010] S1. Preparation of precursor solution:

[0011] Select a suitable iron source as a precursor, and add the iron source and other necessary metal salts or additives to the organic solvent ethanol in proportion, and stir thoroughly until they are completely dissolved to form a stable precursor solution;

[0012] S2. Sol-gel transformation:

[0013] Hydrolysis reaction: Control the reaction conditions to make the metal salt in the precursor solution undergo hydrolysis to generate iron hydroxide (Fe(OH) 3 ) and iron oxide (Fe 2 O 3 );

[0014] Polymerization reaction: The monomers generated by hydrolysis are connected to each other through polymerization reaction to form a sol with a three-dimensional network structure. The particle size, distribution and morphology in the sol will directly affect the performance of the final nanomaterial;

[0015] Gel formation: As the polymerization reaction proceeds, the sol gradually transforms into a gel with a certain strength and rigidity;

[0016] S3. Drying and heat treatment:

[0017] The formed gel is placed in an electric constant temperature drying oven for drying to remove the solvent and water therein, and then the dried gel is heat treated to promote the crystallization and growth of the nanoparticles;

[0018] S4. Acquisition of Nano-laccase:

[0019] After heat treatment, the Fe 3 O 4 The nanozymes are gradually formed and stably exist, and then the nanoparticles (i.e., Fe 3 O 4 The nanozymes were separated from the gel matrix.

[0020] S5. Purification and characterization:

[0021] The separated nanoparticles are purified to remove impurities, and then characterized in structure and properties through various characterization methods including X-ray diffraction and transmission electron microscopy.

[0022] Furthermore, in step S1, the iron source is selected from inorganic iron salts, specifically ferric chloride (FeCl 3 ), one of the following: iron nitrate (Fe(NO3)3).

[0023] Furthermore, in step S1, the raw material preparation ratio of the precursor solution is as follows: 2 grams of ferric chloride (or ferric nitrate), 50 milliliters of ethanol (for dissolving the precursor), and 0.1 grams of zinc nitrate (for adjusting the performance of the nanomaterial), and 0.5 grams of PEG (for improving the stability and dispersibility of the nanomaterial).

[0024] Furthermore, in step S2, the reaction conditions include temperature and pH value, and the reaction temperature is 25-80° C., and the pH value is 8-12.

[0025] Furthermore, in step S3, the drying temperature of the drying treatment is controlled between 50 and 100° C., the drying time is 8 to 10 hours, and the completion of the drying is determined by regular weighing or observing the color and texture changes of the gel to ensure that the solvent in the gel is fully removed and to avoid cracking or deformation of the gel.

[0026] Furthermore, in step S3, the heat treatment specifically adopts an annealing process. For iron-based nanomaterials, the annealing temperature is controlled between 800 and 1200°C. The annealing temperature should be higher than the nucleation temperature of the nanoparticles, but it should be avoided that the nanoparticles agglomerate or sinter. The annealing time is 8 to 12 hours. The length of the annealing time affects the crystallization degree and growth effect of the nanoparticles. The specific time depends on the annealing temperature and the properties of the material. A longer annealing time helps the nanoparticles to crystallize and grow more fully, but it will also increase production costs and energy consumption.

[0027] Furthermore, in step S4, the separation of nanoparticles specifically includes the following process:

[0028] Grinding: The gel is broken into smaller particles by mechanical force. In this process, the gel matrix is ​​gradually refined and nanoparticles are released from the gel.

[0029] Ultrasonic dispersion: The ground gel suspension is placed in an ultrasonic processor. Under the action of ultrasound, strong cavitation effects, microjets and shock waves are generated in the liquid medium. The energy of ultrasound destroys the interaction force between the gel matrix and the nanoparticles, so that the nanoparticles are separated from the gel matrix and evenly dispersed in the liquid medium.

[0030] Furthermore, in step S5, the purification process first converts the impurities into soluble or easily removable substances by chemical reaction, and then removes them by the following means:

[0031] Centrifugal separation: Utilize the difference in density, size or shape between nanoparticles and impurities to separate them through the centrifugal force generated by the centrifuge, and remove impurities with obvious physical properties different from those of nanoparticles;

[0032] Solvent washing: The nanoparticles are suspended in a suitable solvent and the impurities attached to the particle surface are removed by multiple washings;

[0033] Filtration: Use a microporous membrane or ultrafiltration membrane to filter the nanoparticle suspension to retain the nanoparticles and remove impurities in the solution. It is suitable for removing larger particles of impurities.

[0034] Furthermore, in step S5, the characterization method includes:

[0035] X-ray diffraction (XRD): used to determine the crystal structure, phase composition and lattice parameters of nanoparticles. The XRD spectrum can be used to analyze the diffraction peak position, intensity and shape of nanoparticles, thereby inferring their crystal structure and phase purity;

[0036] Transmission electron microscopy (TEM): provides direct observation of the morphology, size and microstructure of nanoparticles. TEM images can clearly show the shape, size, distribution and lattice fringes of nanoparticles.

[0037] Scanning electron microscopy (SEM): Similar to TEM, but SEM is usually used to observe larger samples or surface morphology. SEM images can provide distribution and morphological information of nanoparticles on a macroscopic scale.

[0038] Dynamic light scattering (DLS): used to measure the particle size distribution and zeta potential of nanoparticles in solution. DLS technology infers the particle size of nanoparticles by measuring the change in the intensity of scattered light under laser irradiation, and can evaluate the stability and dispersibility of nanoparticles.

[0039] In a second aspect, an application of an iron-based nano-laccase for removing organic pollutants is applied to the iron-based nano-laccase prepared as described above, characterized in that the specific process is:

[0040] Application environment preparation: Analyze the water quality of water bodies containing organic pollutants to determine the type and concentration of pollutants and the physical and chemical properties of the water bodies such as pH value and temperature. Then, according to the catalytic characteristics of iron-based nano-laccase, adjust the pH value of the water body to 5.5-6.5 and the temperature to 25-60°C to improve the catalytic efficiency of iron-based nano-laccase.

[0041] Addition of iron-based nano-laccase: the dosage of iron-based nano-laccase is comprehensively considered according to factors such as the concentration of pollutants, the volume of the water body, and the catalytic efficiency of the iron-based nano-laccase, and the prepared iron-based nano-laccase is added to the water body containing organic pollutants in a certain proportion;

[0042] Catalytic degradation process: The laccase component in the iron-based nano-laccase will be adsorbed onto the organic pollutant molecules (because the phenols, benzene rings and other structures in the organic pollutant molecules have a high affinity with the active site of the laccase). After adsorption, the laccase catalyzes the redox reaction of the organic pollutants, destroying their unsaturated conjugated system, thereby destroying the molecular structure of the organic pollutants (laccase can catalyze the hydroxylation, carboxylation and other reactions of the phenols, benzene rings and other structures in the organic pollutants), converting them into small molecular compounds that are easier to decompose, and then further decomposed by redox, and finally converted into inorganic substances such as carbon dioxide and water, achieving harmless treatment of organic pollutants;

[0043] Residue treatment: The water body after catalytic degradation is subjected to subsequent treatment, such as sedimentation, filtration, etc., to remove possible residual nanomaterials or other impurities.

[0044] The present invention provides a preparation method of an iron-based nano-laccase and its application in removing organic pollutants, which has the following beneficial effects:

[0045] The present invention optimizes the preparation process of iron-based nano-laccase, improves its synthesis method, improves the purity and crystallinity of iron-based nanoparticles by adopting a sol-gel method, and utilizes advanced nanotechnology and characterization methods, such as transmission electron microscopy, X-ray diffraction, etc., to precisely regulate the structure, morphology and surface properties of the nanoenzyme to achieve specific catalytic performance. The entire preparation method is simpler, more economical and more environmentally friendly, thereby reducing production costs and improving production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 The present invention is a schematic flow chart of the steps of a method for preparing an iron-based nano-laccase;

[0047] Figure 2 This is a table of experimental test results of a method for preparing an iron-based nano-laccase of the present invention and its application in removing organic pollutants. DETAILED DESCRIPTION

[0048] The following embodiments of the present invention are described in further detail in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0049] Embodiment 1

[0050] like Figure 1 As shown, a method for preparing an iron-based nano-laccase comprises the following steps:

[0051] S1. Preparation of precursor solution:

[0052] Choose ferric chloride (FeCl 3) as a precursor, and add the iron source and other necessary metal salts or additives to the organic solvent ethanol in proportion, stir them until they are completely dissolved, and form a stable precursor solution; and the raw material preparation ratio of the precursor solution is as follows: 2 grams of ferric chloride, 50 milliliters of ethanol (for dissolving the precursor), and 0.1 grams of zinc nitrate (for adjusting the performance of the nanomaterial), 0.5 grams of PEG (for improving the stability and dispersibility of the nanomaterial);

[0053] S2. Sol-gel transformation:

[0054] Hydrolysis reaction: The reaction conditions are controlled at a temperature of 70°C and a pH of 10, so that the metal salt in the precursor solution undergoes a hydrolysis reaction to generate iron hydroxide (Fe(OH) 3 ) and iron oxide (Fe 2 O 3 );

[0055] Polymerization reaction: The monomers generated by hydrolysis are connected to each other through polymerization reaction to form a sol with a three-dimensional network structure. The particle size, distribution and morphology in the sol will directly affect the performance of the final nanomaterial;

[0056] Gel formation: As the polymerization reaction proceeds, the sol gradually transforms into a gel with a certain strength and rigidity;

[0057] S3. Drying and heat treatment:

[0058] The formed gel is placed in an electric constant temperature drying oven for drying to remove the solvent and moisture therein. The drying temperature of the drying treatment is controlled between 90°C and the drying time is 10 hours. The drying is completed by regularly weighing or observing the color and texture changes of the gel to ensure that the solvent in the gel is fully removed and to avoid cracking or deformation of the gel. The dried gel is then heat-treated to promote the crystallization and growth of the nanoparticles. The heat treatment specifically adopts an annealing process. For iron-based nanomaterials, the annealing temperature is controlled between 1000°C. The annealing temperature should be higher than the nucleation temperature of the nanoparticles, but should not be too high to cause agglomeration or sintering of the nanoparticles. The annealing time is 10 hours. The length of the annealing time affects the crystallization degree and growth effect of the nanoparticles. The specific time depends on the annealing temperature and the properties of the material. A longer annealing time helps the nanoparticles to crystallize and grow more fully, but it will also increase production costs and energy consumption.

[0059] S4. Acquisition of Nano-laccase:

[0060] After heat treatment, the Fe 3 O 4 The nanozymes are gradually formed and stably exist, and then the nanoparticles (i.e., Fe 3 O4 The separation of nanoparticles includes the following steps:

[0061] Grinding: The gel is broken into smaller particles by mechanical force. In this process, the gel matrix is ​​gradually refined and nanoparticles are released from the gel.

[0062] Ultrasonic dispersion: The ground gel suspension is placed in an ultrasonic processor. Under the action of ultrasound, strong cavitation effects, microjets and shock waves are generated in the liquid medium. The energy of ultrasound destroys the interaction between the gel matrix and the nanoparticles, so that the nanoparticles are separated from the gel matrix and evenly dispersed in the liquid medium.

[0063] S5. Purification and characterization:

[0064] The separated nanoparticles are first converted into soluble or easily removable substances by chemical reactions, and then centrifuged (using the difference in density, size or shape between nanoparticles and impurities to separate them through the centrifugal force generated by the centrifuge, and removing impurities with obvious physical properties different from the nanoparticles), solvent washed (suspending the nanoparticles in an appropriate solvent and removing impurities attached to the surface of the particles through multiple washings), filtered (using a microporous filter membrane or ultrafiltration membrane to filter the nanoparticle suspension to intercept the nanoparticles and remove impurities in the solution, and remove impurities of larger particles), and then characterized by various characterization methods including X-ray diffraction and transmission electron microscopy for structure and performance. The characterization methods include:

[0065] X-ray diffraction (XRD): used to determine the crystal structure, phase composition and lattice parameters of nanoparticles. The XRD spectrum can be used to analyze the diffraction peak position, intensity and shape of nanoparticles, thereby inferring their crystal structure and phase purity;

[0066] Transmission electron microscopy (TEM): provides direct observation of the morphology, size and microstructure of nanoparticles. TEM images can clearly show the shape, size, distribution and lattice fringes of nanoparticles, which is of great significance for studying the structure and properties of nanoparticles.

[0067] Scanning electron microscopy (SEM): Similar to TEM, but SEM is usually used to observe larger samples or surface morphology. SEM images can provide distribution and morphological information of nanoparticles on a macroscopic scale.

[0068] Dynamic light scattering (DLS): used to measure the particle size distribution and zeta potential of nanoparticles in solution. DLS technology infers the particle size of nanoparticles by measuring the change in the intensity of scattered light under laser irradiation, and can evaluate the stability and dispersibility of nanoparticles.

[0069] An application of an iron-based nano-laccase to remove organic pollutants is applied to the iron-based nano-laccase prepared as described above, and the specific process is:

[0070] Application environment preparation: Analyze the water quality of water bodies containing organic pollutants to determine the type and concentration of pollutants and the physical and chemical properties of the water bodies such as pH value and temperature. Then, according to the catalytic characteristics of iron-based nano-laccase, adjust the pH value of the water body to 5.5-6.5 and the temperature to 25-60°C to improve the catalytic efficiency of iron-based nano-laccase.

[0071] Addition of iron-based nano-laccase: the dosage of iron-based nano-laccase is comprehensively considered according to factors such as the concentration of pollutants, the volume of the water body, and the catalytic efficiency of the iron-based nano-laccase, and the prepared iron-based nano-laccase is added to the water body containing organic pollutants in a certain proportion;

[0072] Catalytic degradation process: The laccase component in the iron-based nano-laccase will be adsorbed onto the organic pollutant molecules (because the phenols, benzene rings and other structures in the organic pollutant molecules have a high affinity with the active site of the laccase). After adsorption, the laccase catalyzes the redox reaction of the organic pollutants, destroying their unsaturated conjugated system, thereby destroying the molecular structure of the organic pollutants (laccase can catalyze the hydroxylation, carboxylation and other reactions of the phenols, benzene rings and other structures in the organic pollutants), converting them into small molecular compounds that are easier to decompose, and then further decomposed by redox, and finally converted into inorganic substances such as carbon dioxide and water, achieving harmless treatment of organic pollutants;

[0073] Residue treatment: The water body after catalytic degradation is subjected to subsequent treatment, such as sedimentation, filtration, etc., to remove possible residual nanomaterials or other impurities.

[0074] Comparative Example 1

[0075] An iron-based nano-laccase, which differs from Example 1 in that it is prepared by a preparation method of an iron-based nano-enzyme disclosed in a patent document with publication number CN116099572A, and its application in removing organic pollutants is the same as that in Example 1.

[0076] Comparative Example 2

[0077] An iron-based nano-laccase, which differs from Example 1 in that the iron-based nano-laccase is prepared by the most common co-precipitation method, and its application in removing organic pollutants is the same as that in Example 1.

[0078] The general process of co-precipitation preparation is as follows:

[0079] Solution preparation: Dissolve ferric chloride and zinc nitrate in appropriate amounts of solvent (such as ethanol or deionized water) to form a uniform metal ion solution; PEG can be used as a stabilizer or surfactant and is also added to the solution at this stage;

[0080] Co-precipitation reaction: by adding a precipitant (such as ammonia water, sodium hydroxide, etc.) to the above mixed solution, the iron ions and zinc ions are precipitated simultaneously in the solution;

[0081] Aging and washing: After the coprecipitation reaction is completed, the obtained precipitate is left to stand for a period of time (called aging) at an appropriate temperature to promote the growth and perfection of the crystals; subsequently, the precipitate is separated from the solution by centrifugation, filtration, etc., and washed with deionized water or ethanol several times to remove residual ions and impurities;

[0082] Drying and calcination: The washed precipitate is dried at an appropriate temperature to remove the water and solvent therein, and then calcined as needed to improve the crystallinity and stability of the nanoparticles and possibly form a specific crystal structure or phase;

[0083] Nanozyme formation: After the above steps, the obtained nanoparticles, i.e., iron-based nanolaccases, will exhibit catalytic activity similar to that of natural laccases;

[0084] Experimental testing

[0085] In order to more clearly illustrate the content of the present invention, the total preparation time and preparation results of the iron-based nano-laccase prepared in Example 1 and Comparative Examples 1-2 were statistically analyzed, and the application of the iron-based nano-laccase in removing organic pollutants was tested, wherein the organic pollutants included: volatile organic compounds (phenol was selected as the test item), halogenated hydrocarbons (chloroform was selected as the test item), pesticides and their degradation products (organochlorine pesticide DDT was selected as the test item), and petroleum pollutants (diesel was selected as the test item). The results are shown in FIG. Figure 2 As shown:

[0086] Combination Figure 2 It can be seen that the iron-based nano-laccase prepared in Example 1 takes significantly shorter preparation time and is basically free of impurities, and the prepared Fe 3 O 4 The application effect of the nanozyme in removing organic pollutants is significantly better than that of comparative examples 1-2.

[0087] The embodiments of the present invention are given for the purpose of illustration and description, and are not intended to be exhaustive or to limit the invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described in order to better illustrate the principles and practical applications of the present invention and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.

Claims

1. A method for preparing an iron-based nano-laccase, characterized in that: The following steps are involved: S1. Preparation of precursor solution: Select a suitable iron source as a precursor, and add the iron source and other necessary metal salts or additives to the organic solvent ethanol in proportion, and stir thoroughly until they are completely dissolved to form a stable precursor solution; S2. Sol-gel transformation: Controlling the reaction conditions, the metal salt in the precursor solution undergoes a hydrolysis reaction to generate iron hydroxide and iron oxide, and then the monomers generated by the hydrolysis are connected to each other through a polymerization reaction to form a sol with a three-dimensional network structure, and as the polymerization reaction proceeds, the sol gradually transforms into a gel; S3. Drying and heat treatment: The formed gel is placed in an electric constant temperature drying oven for drying to remove the solvent and water therein, and then the dried gel is heat treated to promote the crystallization and growth of the nanoparticles; S4. Acquisition of Nano-laccase: After heat treatment, Fe3O4-based nanozymes gradually formed and existed stably in the gel, and then the nanoparticles were separated from the gel matrix by grinding and ultrasonic dispersion; S5. Purification and characterization: The separated nanoparticles are purified to remove impurities, and then characterized in structure and properties through various characterization methods including X-ray diffraction and transmission electron microscopy.

2. The method for preparing an iron-based nano-laccase according to claim 1, characterized in that: In the step S1, the iron source is selected from an inorganic iron salt, specifically one of ferric chloride and ferric nitrate.

3. The method for preparing an iron-based nano-laccase according to claim 2, characterized in that: In step S1, the raw material preparation ratio of the precursor solution is as follows: 2 grams of ferric chloride or ferric nitrate, 50 milliliters of ethanol, 0.1 grams of zinc nitrate, and 0.5 grams of PEG.

4. The method for preparing an iron-based nano-laccase according to claim 1, characterized in that: In step S2, the reaction conditions include temperature and pH value, and the reaction temperature is 25-80° C. and the pH value is 8-12.

5. The method for preparing an iron-based nano-laccase according to claim 1, characterized in that: In step S3, the drying temperature of the drying treatment is controlled between 50 and 100° C., the drying time is 8 to 10 hours, and whether the drying is completed is determined by regular weighing or observing the color and texture changes of the gel.

6. The method for preparing an iron-based nano-laccase according to claim 1, characterized in that: In step S3, the heat treatment specifically adopts an annealing process. For iron-based nanomaterials, the annealing temperature is controlled between 800 and 1200° C., and the annealing time is 8 to 12 hours.

7. The method for preparing an iron-based nano-laccase according to claim 1, characterized in that: In step S4, the separation of nanoparticles specifically includes the following process: Grinding: The gel is broken into smaller particles by mechanical force. In this process, the gel matrix is ​​gradually refined and nanoparticles are released from the gel. Ultrasonic dispersion: The ground gel suspension is placed in an ultrasonic processor. Under the action of ultrasound, strong cavitation effects, microjets and shock waves are generated in the liquid medium. The energy of ultrasound destroys the interaction force between the gel matrix and the nanoparticles, so that the nanoparticles are separated from the gel matrix and evenly dispersed in the liquid medium.

8. The method for preparing an iron-based nano-laccase according to claim 1, characterized in that: In step S5, the purification process first converts the impurities into soluble or easily removable substances by chemical reaction, and then removes them by the following means: Centrifugal separation: Utilize the difference in density, size or shape between nanoparticles and impurities to separate them through the centrifugal force generated by the centrifuge, and remove impurities with obvious physical properties different from those of nanoparticles; Solvent washing: The nanoparticles are suspended in a suitable solvent and the impurities attached to the particle surface are removed by multiple washings; Filtration: Use a microporous membrane or ultrafiltration membrane to filter the nanoparticle suspension to retain the nanoparticles and remove impurities in the solution. It is suitable for removing larger particles of impurities.

9. The method for preparing an iron-based nano-laccase according to claim 1, characterized in that: In step S5, the characterization method includes: X-ray diffraction: used to determine the crystal structure, phase composition and lattice parameters of nanoparticles. The X-ray diffraction spectrum can be used to analyze the diffraction peak position, intensity and shape information of nanoparticles, thereby inferring their crystal structure and phase purity; Transmission electron microscopy: provides direct observation of the morphology, size and microstructure of nanoparticles, showing detailed information such as the shape, size, distribution and lattice fringes of nanoparticles; Scanning electron microscopy: Similar to transmission electron microscopy, but used to observe larger samples or surface morphology. SEM images can provide information on the distribution and morphology of nanoparticles on a macroscopic scale. Dynamic light scattering: used to measure the particle size distribution and zeta potential of nanoparticles in solution. Dynamic light scattering technology infers the particle size of nanoparticles by measuring the change in the intensity of scattered light under laser irradiation, and can evaluate the stability and dispersibility of nanoparticles.

10. An application of an iron-based nano-laccase for removing organic pollutants, using the iron-based nano-laccase prepared as claimed in claims 1-9, characterized in that: The specific process is: Application environment preparation: Analyze the water quality of water bodies containing organic pollutants to determine the physical and chemical properties of the pollutants, and then adjust the pH value of the water body to 5.5-6.5 and the temperature to 25-60°C according to the catalytic properties of iron-based nano-laccase; Addition of iron-based nano-laccase: the dosage of iron-based nano-laccase is comprehensively considered according to factors such as the concentration of pollutants, the volume of the water body and the catalytic efficiency of the iron-based nano-laccase, and the prepared iron-based nano-laccase is added to the water body containing organic pollutants in a certain proportion; Catalytic degradation process: The laccase component in the iron-based nano-laccase will be adsorbed onto the organic pollutant molecules. After adsorption, the laccase catalyzes the redox reaction of the organic pollutants, destroying their unsaturated conjugated system, thereby destroying the molecular structure of the organic pollutants and converting them into small molecular compounds that are easier to decompose, which are then further decomposed by redox and finally converted into inorganic substances. Residue treatment: The water body after catalytic degradation is subsequently treated to remove possible residual nanomaterials or other impurities.